2008
DOI: 10.1039/b809189g
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of the reaction mechanism for the phosphate diester hydrolysis using an asymmetric dinuclear metal complex as a biomimetic model of the purple acid phosphatase enzyme

Abstract: In this work we have applied quantum mechanical calculations, at the density functional theory level, to investigate the phosphate diester hydrolysis promoted by a cationic heterodinuclear Fe(III)...Zn(II) complex that mimics the structural and functional properties of the purple acid phosphatase (PAP) enzymes. The hydrolysis of the dimethyl phosphate diester was investigated in the gas phase and in solution by means of the continuum PCM model, using the B3LYP hybrid exchange-correlation functional. Our comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 40 publications
7
34
0
Order By: Relevance
“…In this research field, the hydrolysis of phosphodiester is of paramount importance in biological and industrial processes . Many researchers have been working hard for developing the biomimetic models for metalloenzyme with high efficiency and selectivity to achieve friendly environment and high‐economy processes . Over the rapid development of artificial enzyme mimicking, there has been considerable interest in the metal ion, such as Co(III), Cu(II), Zn(II), Ni(II), and lanthanide (Ln) complexes , promoted hydrolysis of phosphate esters, and as potential catalysts for the detoxification of anticholinesterase agents used in chemical warfare since the metal ions play the important role at catalytic active sites in the phosphate ester hydrolysis .…”
Section: Introductionmentioning
confidence: 99%
“…In this research field, the hydrolysis of phosphodiester is of paramount importance in biological and industrial processes . Many researchers have been working hard for developing the biomimetic models for metalloenzyme with high efficiency and selectivity to achieve friendly environment and high‐economy processes . Over the rapid development of artificial enzyme mimicking, there has been considerable interest in the metal ion, such as Co(III), Cu(II), Zn(II), Ni(II), and lanthanide (Ln) complexes , promoted hydrolysis of phosphate esters, and as potential catalysts for the detoxification of anticholinesterase agents used in chemical warfare since the metal ions play the important role at catalytic active sites in the phosphate ester hydrolysis .…”
Section: Introductionmentioning
confidence: 99%
“…In order to verify the validity of the mechanism and mathematical model proposed above, the observed first-order rate constants (k obsd ) for BNPP hydrolysis as catalysed by the catalytic system were obtained from the experiment with different concentrations of the complex. Based on the experimental data and Eqn (6), the relationship between 1yk obs versus 1=[LaR*] is plotted in Figure 6. According to the intercept and slope of the straight line in Figure 6 obtained by the linear fit of the least-square method, the k cat of 3.40610 À 2 s À 1 and K of 47.29 mol À 1 dm 3 can be evaluated with Eqn (6).…”
Section: Scheme 2 Calculation Of the Correlative Thermodynamic And Kimentioning
confidence: 99%
“…Based on the experimental data and Eqn (6), the relationship between 1yk obs versus 1=[LaR*] is plotted in Figure 6. According to the intercept and slope of the straight line in Figure 6 obtained by the linear fit of the least-square method, the k cat of 3.40610 À 2 s À 1 and K of 47.29 mol À 1 dm 3 can be evaluated with Eqn (6). The curve in Figure 6 show a good linear relationship between the variables, with r 2 40:98, which means that the reaction mechanism proposed in Scheme and the mathematical model above is reasonable.…”
Section: Scheme 2 Calculation Of the Correlative Thermodynamic And Kimentioning
confidence: 99%
“…Much effort has been devoted to developing the biomimetic models for metalloenzymes with high efficiency and selectivity [1 -4]. A variety of different synthetic catalysts for the hydrolysis of DNA and corresponding model substrates have been reported, usually based on lanthanide [4] or transition metal ions [5 -9]. Wide investigations have indicated that the structure of the ligand of the complex plays a key role in designing a mimetic model of the phosphate hydrolase [10 -15].…”
Section: Introductionmentioning
confidence: 99%